2010
DOI: 10.1126/scitranslmed.3000758
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeper Mutations Mediate Resistance to BRAF-Targeted Therapies

Abstract: BRAF is a serine-threonine-specific protein kinase that is mutated in 2% of human cancers. Oncogenic BRAF is a validated therapeutic target that constitutively activates mitogen-activated protein kinase kinase (MEK)-extracellular signal-regulated kinase (ERK) signaling, driving tumor cell proliferation and survival. Drugs designed to target BRAF have been developed, but it is difficult to prove that they mediate their antitumor effects by inhibiting BRAF rather than by working through off-target effects. We ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 42 publications
(72 reference statements)
7
110
0
Order By: Relevance
“…Ba/F3 cells require IL-3 for growth, but this dependence can be overcome by constitutive MAPK activation (11). Previous studies have demonstrated that Ba/F3 cells can be rendered IL-3-independent upon V600E BRAF expression, but not wild-type BRAF expression (12). Accordingly, we were able to demonstrate IL-3 independence in Ba/F3 cells stably expressing the KIAA1549-BRAF fusion constructs (Fig.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Ba/F3 cells require IL-3 for growth, but this dependence can be overcome by constitutive MAPK activation (11). Previous studies have demonstrated that Ba/F3 cells can be rendered IL-3-independent upon V600E BRAF expression, but not wild-type BRAF expression (12). Accordingly, we were able to demonstrate IL-3 independence in Ba/F3 cells stably expressing the KIAA1549-BRAF fusion constructs (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Gateway cloning (Invitrogen) and site-directed mutagenesis were used to generate the following Myctagged constructs: wild-type BRAF, kinase-dead K482M BRAF mutant (KD), BRAF V600E mutant (V600E), HRASV12 mutant (RASV12), and wild-type KIAA1549. Full-length, "long form" KIAA1549-BRAF fusion (Fusion-1) was generated by translationally silent site-directed mutagenesis, providing restriction sites that permitted the construction of the KIAA1549-BRAF gene fusion via restriction digest/subcloning of the N terminus of KIAA1549 (exons [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Fig. 1F).…”
Section: Methodsmentioning
confidence: 99%
“…Within the Rafmitogen-activated protein kinase (MAPK) cascade, potent inhibitors of BRaf, CRaf, and MEK are in clinical use (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Although very encouraging, the clinical responses to Raf inhibitors can be relatively short-lived, with treatment failure and tumor progression occurring due to acquired resistance, primarily as a result of secondary mutations in oncogenic BRaf or other proteins such as N-Ras or MEK (14)(15)(16). In addition, while BRaf inhibitors inhibit the activation of BRaf/MEK/extracellular signal-regulated kinase (ERK) in BRaf mutant cell lines, they paradoxically activate MEK/ ERK signaling in cell lines with Ras mutations (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Approximately 60% of malignant melanomas harbour the BRAF mutation. Although patients with the damaged BRAF are non-responsive to the KRAS/BRAF inhibitor, sorafenib, response to the second-generation drug called PLX4720 is favourable (Whittaker et al 2010). Improved outcomes have also been reported in patients with non-small cell lung cancer (NSCLC) harbouring EGFR mutations treated with the tyrosine kinase inhibitors (TKI) erlotinib and gefitinib (Kim et al 2008;Paz-Ares et al 2010).…”
Section: Biomarker Prognostic Predictivementioning
confidence: 90%